Molecular characterisation of Mycoplasma gallisepticum MGC2 gene from commercial chicken isolates - Ahmad, Kartini; Ideris, Aini; Omar, Abdul Rahman; Tan, C. G. (Veterinary Association Malaysia, 2011)
Mycoplasma gallisepticum (MG), an agent that causes chronic respiratory diseases in the avian, possesses a cytadhesin mgc2 gene. Mgc2 is a second cytadhesin-like protein, localised on the tenninal bleb involved in the attachment of MG to host tissue. Five reference MG strains (S6, R, F, TSll and 6/85) and 18 field isolates were extracted, sequenced and analysed, including another 30 published isolate sequences from V.S., Australia and Israel. The mgc2 gene isolates exhibit high G + C base content of 45% due to the presence of high proline (14 to 16%) and glycine (13 to 14%) residues located at the two-third position of the carboxy terminal region. The Malaysian field isolates were divided into four categories: (i) 854 - 857 bp amplicon, (ii) 837 bp amplicon, (iii) 822 - 824 bp amplicon, and (iv) 791 bp amplicon, due to gene size polymorphism. Six field isolates (KPR44 L, KPR16W 44 L, THNG8W L, AK2 VC, PF3H Br and PF7V Br) exhibited several mutations at the 3' region located at positions 166, 173, 195 and 202 a.a., which distinctively differ from other reference strains but appear identical to Israeli isolates. Other field isolates and certain published sequences were either totally similar or almost similar to MGS6, TS lland 6/85 strains.